Expansion of vegetated coastal ecosystems in the future Arctic - Krause-Jensen, Dorte; Duarte, Carlos M. (Frontiers in Marine Science, 2014)
Warming occurs particularly fast in the Arctic and exerts profound effects on arctic ecosystems. Sea ice-associated ecosystems are projected to decline but reduced arctic sea ice cover also increases the solar radiation reaching the coastal seafloors with the potential for expansion of vegetated habitats, i.e. kelp forests and seagrass meadows. These habitats support key ecosystem functions, some of which may mitigate effects of climate change. Therefore, the likely expansion of vegetated coastal habitats in the Arctic will generate new productive ecosystems, offer habitat for a number of invertebrate and vertebrate species, including provision of refugia for calcifiers from possible threats from ocean acidification, contribute to enhance CO2 sequestration and protect the shoreline from erosion. The development of models allowing quantitative forecasts of the future of vegetated arctic ecosystems requires that key hypotheses underlying such forecasts be tested. Here we propose a set of three key testable hypotheses along with a research agenda for testing them using a broad diversity of approaches, including analyses of paleo-records, space for-time substitutions and experimental studies. The research agenda proposed would provide a solid underpinning to guide forecasts on the spread of marine macrophytes onto the Arctic with climate change and contribute to balance our understanding of climate change impacts on the arctic ecosystem through a focus on the role of engineering species. Anticipating these changes in ecosystem structure and function is key to develop managerial strategies to maximize these ecosystem services in a future warmer Arctic.